2018
DOI: 10.1109/tbme.2017.2778101
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Conductivity Changes During High-Frequency Irreversible Electroporation for Treatment Planning

Abstract: The treatment planning method developed in this study can be translated to H-FIRE treatments of different widths and for different tissue types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 38 publications
4
29
0
2
Order By: Relevance
“…Prior to the onset of electroporation, the high frequency waveforms of H-FIRE penetrate to the intracellular domain more efficiently than their low frequency counterparts used in IRE; this phenomenon has been exploited to target cells with enlarged nuclei, a physical hallmark common in malignant cells, and resulted in lower lethal EFTs in tumor cells [37,38]. More promising still, these higher frequency waveforms mitigate electrical heterogeneities in complex tissues, resulting in more predictable ablations in highly heterogenous tissues such as tumor tissue [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the onset of electroporation, the high frequency waveforms of H-FIRE penetrate to the intracellular domain more efficiently than their low frequency counterparts used in IRE; this phenomenon has been exploited to target cells with enlarged nuclei, a physical hallmark common in malignant cells, and resulted in lower lethal EFTs in tumor cells [37,38]. More promising still, these higher frequency waveforms mitigate electrical heterogeneities in complex tissues, resulting in more predictable ablations in highly heterogenous tissues such as tumor tissue [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…Electric conductivity is a key parameter in the calculation of electric fields. Previous studies demonstrated that electric conductivity dynamically changes from the baseline to higher values in the steps depending on EFS and the temperature [36,41,42]. An electro-thermal coupling function (Equation (4)) was introduced to calculate the electrical conductivity during IRE by Garcia et al [43].…”
Section: Discussionmentioning
confidence: 99%
“…The tissue electrical conductivity was determined using the following equation to incorporate changes due to electroporation and thermal effect [24,26,41,42]:…”
Section: Tissue Electrical Conductivitymentioning
confidence: 99%
See 2 more Smart Citations